Attractiveness of alternative food baits in catching houseflies (Musca domestica L.) (Research, Society and Development, 2022)
Musca domestica L. (Diptera: Muscidae) is an insect that occurs in rural and urban areas and, due to its sanitary relevance, research has been carried out to investigate alternative management methods. This work aimed to evaluate alternative food attractants in the capture of these insects. The study was carried out in a residence in the rural area of ​​the city of Canhotinho-PE, in May 2021. As a trap, 500 mL PET bottles were used, containing juices of: guava (Psidium guajava L.) with 45.2% pulp, mango (Mangifera indica L.) with 50.2%, cashew (Anacardium occidentale L.) 25.3%, passion fruit (Passiflora edulis L.) with 12.0% of pulp present and a commercial product based on methomyl. The Completely Randomized Design (DIC) was used. The results were submitted to analysis of variance (ANOVA), and the means were compared by Tukey's test at 5% probability using the statistical software Sisvar. It was found that the juices of P. edulis and A. occidentale presented higher averages, demonstrating to be more attractive and efficient for capturing this species of fly.